Mechanical Model for Shear Friction Capacity of Concrete at Construction Joints. (24th July 2018) - Kwon, Seung-Jun; Yang, Keun-Hyeok; Mun, Ju-Hyun
Abstract : This study examined the reliability and limitations of code equations for determining the shear friction strength of a concrete interface with construction joints. This was achieved by examining the code equations (ACI 318-14, AASHTO, and fib 2010) and comparing the results predicted by equations with experimental data compiled from 207 push-off specimens (133 rough and 74 smooth construction joints). The integrated mechanical model for the monolithic interface, derived from the upper-bound theorem of concrete plasticity, was also modified to estimate the shear friction strength of the construction joints. The upper limit for shear friction strength was formulated from a concrete crushing failure limit on the strut-and-tie action along the interfacial plane, to avoid overestimating the shear transfer capacity of transverse reinforcement with a high clamping force. Code equations are highly conservative and dispersive in predicting the shear friction strength of rough construction joints and yield large scattering in the data for the ratios between the measured and predicted shear friction strengths. The predictions obtained using the proposed model agreed well with test results, indicating correlating trends with the test results for evaluating the effects of various parameters on the shear friction strength of rough construction joints. According to the proposed model, the values of cohesion and coefficient of friction for concrete could be determined as 0.11 f c ′ 0.65 and 0.64, respectively, for smooth construction joints and 0.27 f c ′ 0.65 and 0.95, respectively, for rough construction joints, where f c ′ is the compressive strength of concrete.